Passages Moving beyond liminality in the study of literature and culture - Kovach, Elizabeth; Kugele, Jens; Nünning, Ansgar (Comparative Literature and Culture, 2022)
The study of literature and culture is marked by various distinct understandings of passages - both as phenomena and critical concepts. These include the anthropological notion of rites of passage, the shopping arcades (Passagen) theorized by Walter Benjamin, the Middle Passage of the Atlantic slave trade, present-day forms of migration and resettlement, and understandings of translation and adaptation. Whether structural, semiotic, spatial/geographic, temporal, existential, societal or institutional, passages refer to processes of (status) change. They enable entrances and exits, arrivals and departures, while they also foster moments of liminality and suspension. They connect and thereby engender difference. This volume is an exploration of passages as contexts and processes within which liminal experiences and encounters are situated. It aims to foster a concept-based, interdisciplinary dialogue on how to approach and theorize such a term. Based on the premise that concepts travel through times, contexts and discursive settings, a conceptual approach to passages provides the authors of this volume with the analytical tools to (re-)focus their research questions and create a meaningful exchange across disciplinary, national and linguistic boundaries. Contributions from senior scholars and early-career researchers whose work focuses on areas such as cultural memory, performativity, space, media, (cultural) translation, ecocriticism, gender and race utilize specific understandings of passages and liminality, reflecting on their value and limits for their research.